2002
DOI: 10.1002/tox.10051
|View full text |Cite
|
Sign up to set email alerts
|

Overview of results from the WaterTox intercalibration and environmental testing phase II program: Part 1, statistical analysis of blind sample testing

Abstract: There is an urgent need to evaluate the presence of toxicants in waters used for human consumption and to develop strategies to reduce and prevent their contamination. The International Development Research Centre undertook an intercalibration project to develop and validate a battery of bioassays for toxicity testing of water samples. The project was carried out in two phases by research institutions from eight countries that formed the WaterTox network. Results for the first phase were reported in the specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
0
15
0
4
Order By: Relevance
“…Bioassays with other invertebrates, such as daphnia (Daphnia magna) and Ceriodaphnia (C. affinis or C. dubia), are widely used to detect chronic toxicity (after 21-days exposure) of chemical solutions, environmental and waste waters (Viganò et al, 1996). In several studies the Hydra bioassay, particularly when chronic changes in morphology and reproduction rate were measured, was more sensitive than other bioassays undertaken with invertebrate, vertebrate and plant test organisms (Diaz-Baez et al, 2002;Ronco et al, 2002a;Arkhipchuk et al, 2006b;Oberholster et al, 2008). In particular, sub-lethal effects on Hydra morphology were found to be considerably more sensitive than lethal effects , closely matching the toxicity response of the fathead minnow (Fu et al, 1994) and are generally more sensitive than the Microtox test (Pardos et al, 1999).…”
Section: Comparison Of Hydra Sensitivity With Other Test Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioassays with other invertebrates, such as daphnia (Daphnia magna) and Ceriodaphnia (C. affinis or C. dubia), are widely used to detect chronic toxicity (after 21-days exposure) of chemical solutions, environmental and waste waters (Viganò et al, 1996). In several studies the Hydra bioassay, particularly when chronic changes in morphology and reproduction rate were measured, was more sensitive than other bioassays undertaken with invertebrate, vertebrate and plant test organisms (Diaz-Baez et al, 2002;Ronco et al, 2002a;Arkhipchuk et al, 2006b;Oberholster et al, 2008). In particular, sub-lethal effects on Hydra morphology were found to be considerably more sensitive than lethal effects , closely matching the toxicity response of the fathead minnow (Fu et al, 1994) and are generally more sensitive than the Microtox test (Pardos et al, 1999).…”
Section: Comparison Of Hydra Sensitivity With Other Test Organismsmentioning
confidence: 99%
“…The core battery of tests consisted of 2 animal assays (48 hour acute toxicity to D. magna (Dutka, 1989) and 96 hour exposure lethality to H. vulgaris, (Trottier et al, 1997) and a vascular plant bioassay (L. sativa 120 hour exposure inhibition of root elongation (Dutka, 1989). This program initially established quality control mechanisms for the bioassays used (Ronco et al, 2002b) followed by examining the sensitivity, applicability and reproducibility of selected battery to screen drinking water and drinking water sources of the presence of toxicants (Diaz-Baez et al, 2002). These bioassays have been subsequently used in several other studies (Arkhipchuk and Garanko, 2002;Oberholster et al, 2008) where Hydra was found to show good sensitivity.…”
Section: Use In Monitoringmentioning
confidence: 99%
“…Given the different number and diversity of samples, results obtained are discussed in general terms and the toxicity is expressed as EC 50 /LC 50 /IC 50 (%, v/v) values. However, throughout this article the toxic responses for the Hydra test are reported in terms of lethality, given the variability observed with the sublethal end point during the blind sample testing control exercise (see Ronco et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…This last bioassay was included based on a new protocol developed during the first phase of the WaterTox project. [23,24] Results showed that water samples produced a toxic response in 24% of the cases. Of seven treated drinking waters, four showed toxicity with at least one bioassay, raising the possibility that treatment processes were unable to remove toxic contaminants.…”
Section: Past Scenariomentioning
confidence: 98%